SIKAP BELA NEGARA DITINJAU DARI PEMAHAMAN SEJARAH NASIONAL INDONESIA DAN NILAI-NILAI KEPAHLAWANAN PROGRAM STUDI PENDIDIKAN SEJARAH FKIP UNS - Wati, Liana; Herimanto, Herimanto; Isawati, Isawati (Candi, 2018)
The objectives of the research are: (1) to determine the relationship between the understanding of national history of Indonesia with the attitude of country defense;(2) to determine the relationship between theheroism values with theattitude of country defense; (3) to determine the relationship between the understanding of national history of Indonesia and heroism values with the attitude of country defense.This research is quantitative descriptive research by drawing conclusions through statistical analysis. The population in this study was all students of class XII IPASMA Muhammadiyah 1 Karanganyar in the academic year of 2016/2017. 134 studentswere taken as the sample by using simple random sampling technique. The data were obtained through a test and questionnaires. The questionnaires were tested firstto know the validity and the reliability of the test. The data analysis technique used in this researchwas multiple linear regression analysis, t-test, F, R2 test, and the relative contribution and effective contribution.The conclusions of the research were as: (1) there waspositive and significantrelationship betweenthe understanding of national history of Indonesia with the attitude of country defense. This result based on the multiple linear regression analysis (t test) noted that tcount> ttable, 2.949 >1.978 and significance value 0.004 <0.05 withrelative contribution 27.669% and effective contribution 5.09%;(2) there was positive and significant relationship between heroism values with the attitude of country defense. This result based on the multiple linear regression analysis (t test) noted that tcount>ttable, 4.686 >1.978 and significance value0.000<0.05 with the relative contribution 72.363% and the effective contribution  13.31%; (3) there was positive and significant understanding of national history of Indonesia and heroism values with the attitude of country defense. This result based on the linear regression analysis (F test) was known that Fcount > Ftable, 14.812 >3.07 and significance value0.000 <0.05. The coefficient of determination (R2) is 0.184. It indicated that the magnitude of the relationship between the understanding of national history of Indonesia and heroism values with the attitude of country defense in class XII IPA SMA Muhammadiyah 1 Karanganyarin the academic year 2016/2017 was 18.4%, while the rest was influenced by other variables.